Mood Choices and Power Relations in a Junior High School EFL Lesson Segment - Hanum Salsabila; Kelik Wachyudi (Universitas Islam Negeri Palopo, 2026)
This study examines how Mood choices realise and negotiate power relations in a short junior high school EFL lesson segment in Indonesia. Drawing on Systemic Functional Linguistics, the study traces the movement from Mood structure to speech function and then to power orientation. The data consist of eight teacher clauses selected from a recorded and verbatim-transcribed lesson segment in which the teacher opened and framed the lesson, checked students' readiness, reviewed previous material, introduced visual or personal content, and gave one directive. Each clause was coded for Mood structure, Mood type, speech function, and power orientation. The analysis shows that declaratives dominate the segment and function to frame the lesson, define shared knowledge, and maintain topic control. Interrogatives provide brief but meaningful response slots, while one imperative, softened by the politeness marker please, directs student action without abandoning rapport. The findings suggest that power in this segment is asymmetrical but moderated: the teacher maintains institutional control while using inclusive, polite, and affiliative language. Although illustrative rather than generalisable, the study contributes micro-level evidence of how Mood choices mediate classroom authority, participation, and character-oriented values in Indonesian EFL interaction.